Consignes aux auteurs: Présentation des articles - Publications, HERMES Science (European Journal of Computational Mechanics, 2001)
The instructions put together below fall into three categories. The editor would be grateful to authors for respecting these indications. At times, the length of this summary may attain a dozen lines. It is to be written in size 9 italie Times. An abstract in French will be joined. The instructions put together below fall into three categories. The editor would be grateful to authorsfor respecting these indications. At times, the length of this summary may attain a dozen lines. It is to be written in size 9 italie Times. An abstract in French will be joined.